Analisis Penggunaan Sistem Informasi Rekapitulasi (SIREKAP) pada Pemilihan Umum di Kota Tanjungpinang Tahun 2024 - Esti Cintanesa; Bismar Arianto; Rizky Octa Putri Charin (Asosiasi Peneliti Dan Pengajar Ilmu Sosial Indonesia, 2025)
Sirekap created to simplify the task of election organizers as a tool to assist the recapitulation process and as a means of publication. During second use, there were still many problems, one of which was in Tanjungpinang City. This research aims to analyze how SIREKAP is used in the general elections in Tanjungpinang City 2024. The method used is a qualitative method with a case study approach and uses data collection techniques through observation, interviews, and documentation. This research uses a theory by DeLone and McLean (2003), with 5 indicators, namely system quality, information quality, service quality, user satisfaction, and net benefits. The finding from this research is that the use of SIREKAP in the general election in Tanjungpinang City 2024 has not gone well. This is caused by the quality of the system, namely the server network, which is not optimal enough to handle the increase in the number of SIREKAP users on election day. This also has an impact on the quality of information being less than optimal in disseminating information so that users are not yet satisfied because SIREKAP is deemed not to have provided significant benefits for the general election in Tanjungpinang City 2024.